Pengaruh Profitabilitas Fixed Asset Ratio, Kontrol Kepemilikan dan Struktur Aktiva terhadap Struktur Modal pada Perusahaan Manufaktur di Indonesia - Hasa Nurrohim KP (Universitas Islam Indonesia, 2008)
The objective of this article is to identify the determinant influencing the capital structure of manufactured enterprises in Jakarta Stock Exchange for the years 2001 - 2005. This study uses ordinary least square regression to test whether capital structure (proxy long term debt/total asset) is impacted by various variables, namely profitability, fixed asset ratio, ownership’s control and assets structure. Empirical results show that manufactured enterprises employ mostly long term liabilities to finance their operations. An ownership’s control and profitability also affects the way a manufactured enterprises its operations. Fixed asset ratio and assets structure seems to have no significant impact on the capital structure of Indonesian manufactured enterprises. Keyword: Capital Structure, Profitability, Fixed Asset Ratio, Ownership Control, Assets Structure.